2023
DOI: 10.3389/fpsyt.2022.990216
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of job satisfaction between psychological capital and work engagement among Chinese nurses during COVID-19 outbreak: A comparative study between nurse specialists and general nurses

Abstract: BackgroundThe outbreak of COVID-19 has become a global public health emergency, causing great psychological distress to nurses. It is unknown whether the pandemic will affect the work engagement of nurses, the relationship between psychological capital, job satisfaction, and work engagement among nurses, and whether there are differences between nurse specialists and general nurses during the pandemic.ObjectivesThe purpose of this study was to compare psychological capital, job satisfaction, and work engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 69 publications
1
16
0
3
Order By: Relevance
“…21 Individuals with higher PsyCap have higher work engagement as they are better equipped to deal with adverse factors and have a positive attitude towards work. 22,23 The JD-R model suggests that both job resources and personal resources have important effects on work engagement. The conservation of resources (COR) theory claims that resources, or resource shortages, tend to exist in clusters, rather than in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…21 Individuals with higher PsyCap have higher work engagement as they are better equipped to deal with adverse factors and have a positive attitude towards work. 22,23 The JD-R model suggests that both job resources and personal resources have important effects on work engagement. The conservation of resources (COR) theory claims that resources, or resource shortages, tend to exist in clusters, rather than in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…RNs reporting higher PsyCap scores have also reported higher work engagement in 11 studies (Bonner, 2016; Flinkman et al, 2023; Grover et al, 2018; Jin et al, 2022; Lu et al, 2023; Pan et al, 2017; Shaheen et al, 2019; Tian et al, 2023; Wang et al, 2017; Wu & Lee, 2020; Zhang et al, 2023). Furthermore, RNs indicating higher PsyCap, have reported higher organizational commitment (Huo et al, 2020; Peng et al, 2013; Zhou, Yang, et al, 2018), affective commitment (Brunetto, Rodwell, et al, 2016) and a higher intention to remain in the organization (Luthans & Jensen, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al revealed that the indirect effect of satisfaction was signi cant in that nurses' career identity in uenced turnover intention [23]. Other studies also proved the mediating effect of job satisfaction on outcomes such as work engagement and quality of nursing care [24,27]. Job satisfaction is a determinant of nurses' productivity and therefore quality of healthcare since it is the state of favorable feelings and well-being of workers in their workspace [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is well known that job burnout has a negative association with job satisfaction [20][21][22]. Several studies including nurses con rm the mediating role of job satisfaction between work-related variables, such as career identity, turnover intention, workload, quality of care, job performance, and professional identity [23][24][25][26][27]. Since the mediating role of nurses' job satisfaction in the relationship between job burnout and quiet quitting is unknown, we hypothesized the following: Hypothesis 2 Nurses' job satisfaction would mediate the relationship between job burnout and their quiet quitting.…”
Section: Introductionmentioning
confidence: 99%